WREN : writing in English : advanced English writing skills for Dutch speakers - Chan, David, 1967-; Jooken, Lieve, 1967-; Robberecht, Paul, 1951- (Gent : Academia Press, 2016)
Writing in English (or ‘Wren' for short) is primarily aimed at university/university-college students whose mother-tongue is Dutch and who wish to develop their English writing skills across a range of genres at an advanced level. Volume I provides detailed guidance on core writing skills (note-taking, paraphrasing, cohesion, register and expression) and covers a range of academic and non-academic genres (summary, essay, review, letters and e-mails). Volume II offers a battery of exercises with solutions to help students develop the necessary skills for effective written communication.
Eng.
Keywords: Schrijfvaardigheden -- Engels